Digital transformation of pathology - the European Society of Pathology expert opinion paper - Eloy, Catarina; Fraggetta, Filippo; van Diest, Paul J; Polónia, António; Curado, Mónica; Temprana-Salvador, Jordi; Zlobec, Inti; Purqueras, Elvira; Weis, Cleo-Aron; Matias-Guiu, Xavier; Schirmacher, Peter; Ryška, Aleš (Virchows Archiv, 2025)
An expert group mandated by the European Society of Pathology (ESP) outlines its recommendations on the digital transformation of pathology departments, aiming to facilitate the acquisition of resources for better patient care. This statement is directed at pathology professionals, offering guidance for the safe implementation of digital pathology while emphasizing the necessity of standardization, quality control, and sustainability. Digital pathology involves automating and standardizing laboratory workflows to produce high-quality whole slide images (WSIs), which are crucial for diagnosis, research, and education. A successful digital transformation requires a multidisciplinary approach, significant investment in human, structural, and informatic resources, and progressive adaptation of laboratory workflows. Key components include robust infrastructure; continuous training; and clear policies for hardware renewal, data storage, and interoperability. The transition demands attention to quality and production control, ensuring efficient WSI generation and timely diagnostic reporting. ESP strongly recommends that pathology departments, supported by funding organizations, start to prioritize digital transformation as a step toward improved patient care and in alignment with global healthcare initiatives. Collaboration, investment, and adherence to quality standards are critical to benefiting the most the full potential of digital pathology.
Keywords: Digital transformation; Digital pathology; Recommendations